Optical Coherence Tomography in a Cohort of Genetically Defined Hereditary Spastic Paraplegia: A Brief Research Report - Vavla, Marinela; Paparella, Gabriella; Papayannis, Alessandro; Pascuzzo, Riccardo; Girardi, Giulia; Pellegrini, Francesco; Capello, Gianluca; Prosdocimo, Gianni; Martinuzzi, Andrea (Frontiers in Neurology, 2019)
Introduction: In-vivo objective documentation of pathological changes in neurodegenerative disease is a major aim to possibly improve our ability to monitor disease progression and response to treatment. Temporal thinning of the retinal nerve fibre layer (RNFL) thickness shown by spectral domain optical coherence tomography (SD-OCT) has been reported in association to the complex forms in hereditary spastic paraplegia (HSP). We performed an assessment of the RNFL thickness in a group of HSP patients, including a longitudinal follow-up in a subgroup. Our aim was to measure and compare the changes and correlate them to clinical progression. Materials & Methods: Twenty-three HSP patients were recruited and studied with the SD-OCT including papillary and macular scan by Spectralis. The clinical severity was assessed using the Spastic Paraplegia Rating Scale. Results: Thinning of the superior, nasal and inferior quadrants bilaterally were observed compared to the normative data in both pure and complicated forms, that was frankly pathological only in a proportion of cases. Thinning correlated with age and disease duration but not with clinical severity. The longitudinal study (n=9) showed no significant change as compared to the baseline data for the period of observation (mean 10.7 months). Conclusions: RFNL is frequently thinned in HSP with no specific recognizable pattern of quadrants involved and SPG types. The small sample size and the short follow-up time showed no clear progression. Although SD-OCT appraisal of RFNL deserves to be explored in neurodegenerative conditions, it might not be suitable for use as a biomarker in HSP as it appears not specific to this condition and can be a feature of aging.